Online Medical Records: A Decade of Experience - Safran, C.; Sands, D. Z.; Rind, D. M. (Methods of Information in Medicine, 1999)
The electronic patient record at the Beth Israel Deaconess Medical Center has fundamentally changed the practice of medicine in ways that its developers never foresaw. This type of highly interactive and work flow enabled program is creating new collaborative roles for computers in complex organizations [4]. With the system able to supervise and monitor care, computers are able to perform many care coordination and documentation functions, freeing people to concentrate more on interpersonal interactions and provision of health care services. One of the challenges in the design of electronic patient records to assist health care providers is how to support collaboration while not requiring that people meet face-to-face. Moreover, a greater challenge for each of us as clinicians is to use this technology as a bridge (rather than a barrier) towards better patient-doctor relationships.
Keywords: Electronic Patient Records; Guidelines; Collaborative Practice Models